Biotreated conventional concrete and CDW-concrete by use of microbial mixed cultures bioproducts - Garcia-Gonzalez, Julia (2018)
a STSM Grant from the COST Action CA15202. and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER –007265; POCI-01-0145-FEDER-007728).